Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species - Cong, Peixin; Li, Houhun (Zootaxa, 2017)
The genus Prays Hübner, 1825 from China is reviewed. Nineteen species are treated, including twelve species described as new: P. orthacantha sp. nov., P. spiniprocessa sp. nov., P. erromera sp. nov., P. rectangula sp. nov., P. tauricornis sp. nov., P. longisaccula sp. nov., P. bisechinata sp. nov., P. semilunata sp. nov., P. semicircularis sp. nov., P. dorsiprotrusa sp. nov., P. helanshana sp. nov., and P. acinacea sp. nov. The female of P. inconspicua Yu et Li, 2004 is described for the first time. Images of adults and genitalia are provided, along with a key to separate all the Chinese species.